Chrysin Induced Cell Apoptosis Through H19/let-7a/COPB2 Axis in Gastric Cancer Cells and Inhibited Tumor Growth - Chen, Lin; Li, Qirong; Jiang, Ziping; Li, Chengshun; Hu, Haobo; Wang, Tiedong; Gao, Yan; Wang, Dongxu (Frontiers in Oncology, 2021)
Background: Chrysin is a natural flavone that is present in honey and has exhibited anti-tumor properties. It has been widely studied as a therapeutic agent for the treatment of various types of cancers. The objectives of this present study were to elucidate how chrysin regulates non-coding RNA expression to exert anti-tumor effects in gastric cancer cells. Methods: Through the use of RNA sequencing, we investigated the differential expression of mRNAs in gastric cancer cells treated with chrysin. Furthermore, COPB2, H19 and let-7a overexpression and knockdown were conducted. Other features, including cell growth, apoptosis, migration and invasion, were also analyzed. Knockout of the COPB2 gene was generated using the CRISPR/Cas9 system for tumor growth analysis in vivo. Results: Our results identified COPB2 as a differentially expressed mRNA that is down-regulated following treatment with chrysin. Moreover, the results showed that chrysin can induce cellular apoptosis and inhibit cell migration and invasion. To further determine the underlying mechanism of COPB2 expression, we investigated the expression of the long non-coding RNA (lncRNA) H19 and microRNA let-7a. Our results showed that treatment with chrysin significantly increased let-7a expression and reduced the expression of H19 and COPB2. In addition, our results demonstrated that reduced expression of COPB2 markedly promotes cell apoptosis. Finally, in vivo data suggested that COPB2 expression is related to tumor growth. Conclusions: This study suggests that chrysin exhibited anti-tumor effects through a H19/let-7a/COPB2 axis.